Can Central Asia be integrated as asean? - Iskakova, Zhainara; Sarsembayev, Marat; Kakenova, Zarina (Opción, 2018)
This article examines the role of the one of the most influentialcontemporary regional political and economic organization of the Associationof Southeast Asian Nations (ASEAN) as an example for further integration of Central Asian countries: Kazakhstan, Kyrgyzstan, Tajikistan, Turkmenistan,and Uzbekistan. The role of security organizations in the context ofintegration also has been used. Based on the findings of this paper, Asiancountries have sufficient resources and motivation to prepare for sustainablecontinental convergence by establishing a meaningful relationship betweenthe experiences of different regionalism in Asia.